Sexual preference modulates attentional bias towards attractive faces in men, but not women - Johanna M. Bellue; David Terburg; Mirre E. Balke; Tessa W. Coster; Jorg J.M. Massen; Tom S. Roth (Evolution and Human Behavior, 2026)

Late-Holocene sediment dynamics and contaminants in the Fecht River, Vosges Mountains, France: From medieval mining to modern floodplains - Charlotte E. Engelmann; Frank Preusser; Alexander Fülling; Gilles Rixhon; Damien Ertlen; Kristin Steger; Raphael Longoni; Isa-Yael Roth; Jan H. Blöthe (CATENA, 2026)

Between evidence and allegation: factual accuracy in discussions on fluoride toxicity and research integrity - Andrea Buettner; Patrick Diel; Gerhard Eisenbrand; Bernd Epe; Petra Först; Tilman Grune; Sabine Guth; Dirk Haller; Volker Heinz; Michael Hellwig; Hans-Ulrich Humpf; Henry Jäger; et al. (Archives of Toxicology, 2026)

Vitamin E supplementation moderates salt-induced oxidation status in beef - Eylon Asido; Jonathan Shalev; Joseph Kanner; David E. Gerrard; Zvi Roth; Oren Tirosh (Meat Science, 2026)

Assessing uncertainty in conservation practice performance: effect of sample frequency on bioreactor nitrate removal - Mark R. Williams; Laura E. Christianson; Kevin W. King; Reid D. Christianson; Jason Roth; Gary W. Feyereisen (Environmental Monitoring and Assessment, 2026)

A Systematic Review and Meta-Analysis of the Use of the National Institutes of Health Toolbox Cognition Battery in Clinical Populations - Kelly H. Watson; Abagail E. Ciriegio; Claire F. Miller; Marissa C. Roth; Bruce E. Compas (Neuropsychology Review, 2026)
The National Institutes of Health Toolbox Cognition Battery (NIHTB-CB) is an assessment tool that has been widely utilized in research with clinical populations across the lifespan. Despite its widespread use, a systematic review and meta-analysis of cognitive function utilizing this battery in clinical samples has not been reported. To address this gap, 84 studies were identified after systematically searching PsycINFO, PubMed, and ProQuest (71 peer-reviewed articles, 11 dissertations, 2 master’s theses) comprising 6331 clinical participants. Study quality was assessed using the QUADAS-2 tool. Results identified significant deficits in the Fluid Cognition Composite and the associated subtests (attention, working memory, processing speed, executive function) in clinical samples when compared to both the NIHTB-CB normative data and recruited comparison samples. Unexpectedly, there was some evidence that clinical participants scored higher on Crystallized Cognition subtests than the normative data but scored significantly lower than recruited controls. There was mixed evidence for performance differences on a Total Cognition Composite measure of cognitive function. There was some evidence of publication bias, and results were moderated by study quality and participant demographics. The implications of the findings for clinical research settings are discussed and suggested future directions are provided.

Variability in Fecundity–Body Size Relationships for Atlantic Salmon Associated With Body Condition and Life History - Tara L. Imlay; Cindy Breau; Julien April; J. Brian Dempson; John Hayward; Jason LeBlanc; Jenny E. Reid; David Roth; Jamie T. Vallis; Travis E. Van Leeuwen; Laura K. Weir (Fisheries Management and Ecology, 2026)
While body size is the primary driver of fecundity, other factors may contribute to variation in these relationships. Anadromous populations of Atlantic salmon ( Salmo salar ) have diverse life histories, and fisheries management relies on accurate fecundity estimates. We used Bayesian hierarchical models to determine the relationship between fecundity and fork length, and other life‐history characteristics, for 25 spawning populations throughout Eastern Canada. Fecundity was best modeled at the river level, increased with body size and condition, and decreased with mean egg diameter. Fecundity was higher for individuals that spent fewer years in freshwater as juveniles, and for consecutive repeat spawners compared with first‐time (or maiden) spawners that spent 1 year in the ocean. Lastly, there was interannual variability in the fecundity–body size relationship. These relationships should be used in conjunction with data on recent changes in body size and/or life‐history traits of populations to inform stock management.

Process-based cost assessment of electrochemical metals recovery from municipal solid waste incineration ash - Jacqueline E. Baidoo; Richard Roth; Duhan Zhang; Michael J. Wang; Yet-Ming Chiang; Elsa A. Olivetti (Waste Management, 2026)

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Cognitive Intra-individual Variability in Cognitively Healthy APOE ε4 Carriers, Mild Cognitive Impairment, and Alzheimer’s Disease: a Meta-analysis - Stephen L. Aita; Victor A. Del Bene; Donald L. Knapp; Claire E. Demming; Vasilios C. Ikonomou; Tyler Owen; Ivan A. Campbell; Bailey N. Wagaman; Nicholas C. Borgogna; Joshua E. Caron; Robert M. Roth; Benjamin D. Hill (Neuropsychology Review, 2025)

Recovery of ecosystem carbon pools 35 years after whole-tree and stem-only clearcutting a red spruce – balsam fir forest in north-central Maine, USA - Inge Stupak; Bruna Barusco; Russell D. Briggs; Ivan J. Fernandez; Shawn Fraver; Agnė Grigaitė; Christopher Preece; Brian E. Roth; C. Tattersall Smith (Forest Ecology and Management, 2025)

Time-dependent fluxes and emission factors of volatile organic compounds from pig manure and solid/liquid digestates - E. Roth; C. Tape; P. Michonneau; A. Chakir (Science of The Total Environment, 2025)

Air pollution exposure assessment for preschool children: Addressing spatial and temporal variations and social inequities - Å.K. Watne; M. Azzouz; P. Molnar; L. Stockfelt; J. Lindén; E. Johansson; M. Laurelin; T. Wisell; H. Lundström; A. Roth; S. Jutterström; J. Moldanova; et al. (Journal of Environmental Management, 2025)

Temperature dependent rate constants for the gas phase reactions of OH radical with first generation products of monoterpenes oxidation: nopinone, limononaldehyde, myrtenal and ketolimonene - M. Fakih; A. Abou-Dib; A. Chakir; E. Roth (Atmospheric Environment, 2025)

Machine learning-based analysis of workers' exposure and detection to volatile organic compounds (VOC) - A. Eid; S. Jodeh; A. Chakir; G. Hanbali; E. Roth (International Journal of Environmental Science and Technology, 2025)

Oil and gas produced water for cattle, crops, and surface water discharge: Evaluation of chemistry, toxicity and economics - Marin E. Wiltse; Brooke Ballenger; Connor B. Stewart; Tamzin A. Blewett; Claire Wadler; Holly K. Roth; Maelle Coupannec; Huma Tariq Malik; Pei Xu; Yeinner Tarazona; Yanyan Zhang; Ralf Sudowe; et al. (Journal of Hazardous Materials, 2025)

Long-term field study on corn response to sulfur fertilization in Iowa, USA - Cecilia Crespo; John L. Kovar; Chad E. Hart; Richard T. Roth; Peter L. O’Brien; Sabrina J. Ruis (Field Crops Research, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Assessing predictions on fitness effects of missense variants in HMBS in CAGI6 - Jing Zhang; Lisa Kinch; Panagiotis Katsonis; Olivier Lichtarge; Milind Jagota; Yun S. Song; Yuanfei Sun; Yang Shen; Nurdan Kuru; Onur Dereli; Ogun Adebali; Muttaqi Ahmad Alladin; et al. (Human Genetics, 2025)

Centenarians—the way to healthy vascular ageing and longevity: a review from VascAgeNet - Sabrina Summer; Maria Borrell-Pages; Rosa-Maria Bruno; Rachel E. Climie; Konstantina Dipla; Aysenur Dogan; Kseniia Eruslanova; Emil Fraenkel; Francesco Mattace-Raso; Christopher J. A. Pugh; Keith D. Rochfort; Mark Ross; et al. (GeroScience, 2024)
The prevalence of centenarians, people who lived 100 years and longer, is steadily growing in the last decades. This exceptional longevity is based on multifaceted processes influenced by a combination of intrinsic and extrinsic factors such as sex, (epi-)genetic factors, gut microbiota, cellular metabolism, exposure to oxidative stress, immune status, cardiovascular risk factors, environmental factors, and lifestyle behavior. Epidemiologically, the incidence rate of cardiovascular diseases is reduced in healthy centenarians along with late onset of age-related diseases compared with the general aged population. Understanding the mechanisms that affect vascular ageing in centenarians and the underlying factors could offer valuable insights for developing strategies to improve overall healthy life span in the elderly. This review discusses these key factors influencing vascular ageing and how their modulation could foster healthy longevity.

P19-70 Gaps and needs analysis, barriers, opportunities and drivers for implementation of Artificial Intelligence and Machine Learning (AI/ML) tools in regulatory risk assessment - S. Kolesnyk; A. Bearth; N. Roth; E. Fritsche; M.F. Wilks (Toxicology Letters, 2024)

Modeling of micron-sized aluminum particle combustion in hot gas flow - S. Feng; Y. Qiu; S. Xu; Z. Wu; C. Ruan; A. Roth; E. Nilsson; E. Berrocal; Z.S. Li; M. Alden; X.S. Bai (Fuel, 2024)

Cover crop impacts on nitrogen losses and environmental damage cost - Frank E. Johnson; Richard T. Roth; Michael D. Ruffatti; Shalamar D. Armstrong (Agriculture, Ecosystems & Environment, 2024)

Geographic distribution of the Cross Seamount beaked whale based on acoustic detections - Jennifer L. K. McCullough; E. Elizabeth Henderson; Jennifer S. Trickey; Jay Barlow; Simone Baumann‐Pickering; Roanne Manzano‐Roth; Gabriela Alongi; Stephen Martin; Selene Fregosi; David K. Mellinger; Holger Klinck; Angela R. Szesciorka; et al. (Marine Mammal Science, 2024)
Beaked whales produce frequency‐modulated echolocation pulses that appear to be species‐specific, allowing passive acoustic monitoring to play a role in understanding spatio‐temporal patterns. The Cross Seamount beaked whale is known only from its unique echolocation signal (BWC) with no confirmed species identification. This beaked whale spans the Pacific Ocean from the Mariana Archipelago to Baja California, Mexico, south to the equator, but only as far north as latitude 29°N. Within these warm waters, 92% of BWC detections occurred at night, 6% during crepuscular periods, and only 2% during daylight hours. Detections of BWC signals on drifting recorders with a vertical hydrophone array at 150 m depth demonstrated that foraging often occurred shallow in the water column (

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Low circulating adropin concentrations predict increased risk of cognitive decline in community-dwelling older adults - Geetika Aggarwal; John E. Morley; Bruno Vellas; Andrew D. Nguyen; Andrew A. Butler; Sophie Guyonnet; Isabelle Carrié; Lauréane Brigitte; Catherine Faisant; Françoise Lala; Julien Delrieu; Hélène Villars; et al. (GeroScience, 2023)
The secreted peptide adropin is highly expressed in human brain tissues and correlates with RNA and proteomic risk indicators for dementia. Here we report that plasma adropin concentrations predict risk for cognitive decline in the Multidomain Alzheimer Preventive Trial (ClinicalTrials.gov Identifier, NCT00672685; mean age 75.8y, SD = 4.5 years, 60.2% female, n = 452). Cognitive ability was evaluated using a composite cognitive score (CCS) that assessed four domains: memory, language, executive function, and orientation. Relationships between plasma adropin concentrations and changes in CCS (∆CCS) were examined using Cox Proportional Hazards Regression, or by grouping into tertiles ranked low to high by adropin values and controlling for age, time between baseline and final visits, baseline CCS, and other risk factors (e.g., education, medication, APOE4 status). Risk of cognitive decline (defined as a ∆CCS of − 0.3 or more) decreased with increasing plasma adropin concentrations (hazard ratio = 0.873, 95% CI 0.780–0.977, P = 0.018). Between adropin tertiles, ∆CCS was significantly different ( P = 0.01; estimated marginal mean ± SE for the 1st to 3rd tertile, − 0.317 ± 0.064; − 0.275 ± 0.063; − 0.042 ± 0.071; n = 133,146, and 130, respectively; P < 0.05 for 1st vs. 2nd and 3rd adropin tertiles). Normalized plasma Aß 42/40 ratio and plasma neurofilament light chain, indicators of neurodegeneration, were significantly different between adropin tertile. These differences were consistent with reduced risk of cognitive decline with higher plasma adropin levels. Overall, these results suggest cognitive decline is reduced in community-dwelling older adults with higher circulating adropin levels. Further studies are needed to determine the underlying causes of the relationship and whether increasing adropin levels can delay cognitive decline.

Description of two cultivated and two uncultivated new Salinibacter species, one named following the rules of the bacteriological code: Salinibacter grassmerensis sp. nov.; and three named following the rules of the SeqCode: Salinibacter pepae sp. nov., Salinibacter abyssi sp. nov., and Salinibacter pampae sp. nov. - Tomeu Viver; Roth E. Conrad; Marianna Lucio; Mourad Harir; Mercedes Urdiain; Juan F. Gago; Ana Suárez-Suárez; Esteban Bustos-Caparros; Rodrigo Sanchez-Martinez; Eva Mayol; Federico Fassetta; Jinfeng Pang; et al. (Systematic and Applied Microbiology, 2023)

Environment-induced heat stress causes structural and biochemical changes in the heart - Melissa Roths; Alyssa D. Freestone; Tori E. Rudolph; Alyona Michael; Lance H. Baumgard; Joshua T. Selsby (Journal of Thermal Biology, 2023)

Evaluation of the genotoxic potential of acrylamide: Arguments for the derivation of a tolerable daily intake (TDI value) - Sabine Guth; Matthias Baum; Alexander T. Cartus; Patrick Diel; Karl-Heinz Engel; Barbara Engeli; Bernd Epe; Tilman Grune; Dirk Haller; Volker Heinz; Michael Hellwig; Jan G. Hengstler; et al. (Food and Chemical Toxicology, 2023)

Chemical Stability and Bioactivity of tanshinone I, tanshinone IIA, cryptotanshinone and dihydrotanshinone in in vitro test systems - Annika Roth; Piwen Zhao; Sebastian T. Soukup; Claudia Guigas; Joachim Stärke; Sabine E. Kulling; Patrick Diel (Toxicology Letters, 2023)

Quantifying the drivers of long‐term prices in materials supply chains - Karan Bhuwalka; Randolph E. Kirchain; Elsa A. Olivetti; Richard Roth (Journal of Industrial Ecology, 2023)
Raw materials costs form an increasingly significant proportion of the total costs of renewable energy technologies that must be adopted at unprecedented rates to combat climate change. As the affordable deployment of these technologies grows vulnerable to materials price changes, effective strategies must be identified to mitigate the risk of higher input costs faced by manufacturers. To better understand potential threats to deployment, a market modeling approach was developed to quantify economic risk factors including material demand, substitutability, recycling, mining productivity, resource quality, and discovery. Results demonstrate that price changes are determined by interactions between demand growth, mining productivity, and resource quality. In the worst cases with high demand and low productivity, development of material substitutes and large recycling rates help reduce the prevalence of price risk from over 90% to under 10%. Investing in these strategies yields significant benefits for manufacturers and governments concerned about costs of materials critical to decarbonization and other advanced technologies.

A hierarchical Bayesian regression model that reduces uncertainty in material demand predictions - Karan Bhuwalka; Eunseo Choi; Elizabeth A. Moore; Richard Roth; Randolph E. Kirchain; Elsa A. Olivetti (Journal of Industrial Ecology, 2023)
Predictions of metal consumption are vital for criticality assessments and sustainability analyses. Although demand for a material varies strongly by region and end‐use sector, statistical models of demand typically predict demand using regression analyses at an aggregated global level (“fully pooled models”). “Un‐pooled” regression models that predict demand at a disaggregated country or regional level face challenges due to limited data availability and large uncertainty. In this paper, we propose a Bayesian hierarchical model that can simultaneously identify heterogeneous demand parameters (like price and income elasticities) for individual regions and sectors, as well as global parameters. We demonstrate the model's value by estimating income and price elasticity of copper demand in five sectors (Transportation, Electrical, Construction, Manufacturing, and Other) and five regions (North America, Europe, Japan, China, and Rest of World). To validate the benefits of the Bayesian approach, we compare the model to both a “fully pooled” and an “un‐pooled” model. The Bayesian model can predict global demand with similar uncertainty as a fully pooled regression model, while additionally capturing regional heterogeneity in income elasticity of demand. Compared to un‐pooled models that predict demand for individual countries and sectors separately, our model reduces the uncertainty of parameter estimates by more than 50%. The hierarchical Bayesian modeling approach we propose can be used for various commodities, improving material demand projections used to study the impact of policies on mining sector emissions and informing investment in critical material production.

Tailored fabrication of quasi-isoporous and double layered α-Fe2O3 thin films and their application in photovoltaic devices - Shanshan Yin; Yuqin Zou; Manuel A. Reus; Xinyu Jiang; Suo Tu; Ting Tian; Ruoxuan Qi; Zhuijun Xu; Suzhe Liang; Yajun Cheng; Julian E. Heger; Matthias Schwartzkopf; et al. (Chemical Engineering Journal, 2023)

Dive characteristics of Cross Seamount beaked whales from long‐term passive acoustic monitoring at the Pacific Missile Range Facility, Kauaʻi - Roanne Manzano‐Roth; E. Elizabeth Henderson; Gabriela C. Alongi; Cameron R. Martin; Stephen W. Martin; Brian Matsuyama (Marine Mammal Science, 2023)
Beaked whale foraging pulses were detected on the Pacific Missile Range Facility (PMRF) off Kauaʻi, Hawaiʻi, via long term passive acoustic monitoring. The unidentified pulses do not match foraging pulses of known species on the range but are similar to the unidentified beaked whale first detected at Cross Seamount, Hawaiʻi. Although there has not been a visual confirmation of the unidentified beaked whale species, analysis of data collected from 2007 to 2019 has identified beaked whale foraging dive characteristics from echolocation pulses. From the 13 years of data, the most distinct patterns were that all foraging dives occurred at night and the nighttime foraging dive rate was 0.11 group vocal periods (GVP) per hour, with most detections on shallow hydrophones (625–1,000 m deep) over steep bathymetric slopes. Data collected during U.S. Navy training events were used to compare dive behavior during mid‐frequency active sonar (MFAS) activity against baseline periods; it was determined that the whales reduced GVPs during sonar and these remained low for at least 3 days after the training events. These results are the first long‐term record of acoustic signals from the Cross Seamount beaked whale and provide important insights into their habitat use and occurrence patterns.

Design and Evaluation of Coastal Web Atlases: Best Practices and Future Opportunities for Map Representation, Interaction, and Usability - David A. Hart; Timothy Prestby; Robert E. Roth (Coastal Management, 2022)

Stellungnahme zu Acetaldehyd als Aromastoff: Aspekte der Risikobewertung - Jan G. Hengstler; Matthias Baum; Alexander T. Cartus; Patrick Diel; Gerhard Eisenbrand; Karl-Heinz Engel; Barbara Engeli; Bernd Epe; Tilman Grune; Sabine Guth; Dirk Haller; Volker Heinz; et al. (Journal of Consumer Protection and Food Safety, 2022)
Opinion on acetaldehyde as a flavouring substance: considerations for risk assessment Acetaldehyde occurs naturally in many foods and is also used as a flavouring due to its fruity aroma. The International Agency for Research on Cancer (IARC) classified acetaldehyde as possibly carcinogenic to humans and, in combination with oral intake via alcoholic beverages, as carcinogenic to humans. Therefore, the question arises whether the use of acetaldehyde as a flavouring agent is still justifiable. The Senate Commission on Food Safety (SKLM) of the German Research Foundation (DFG) reviewed the scientific basis for health risk assessment of the use of acetaldehyde as a flavouring substance and adopted an opinion. Based on the available data, it is at present not possible to conclude if acetaldehyde is genotoxic and mutagenic in vivo after oral exposure. There is also uncertainty regarding the contribution of acetaldehyde as a flavouring substance to the overall exposure to acetaldehyde. Therefore, a science-based assessment on health risk related to the use of acetaldehyde as a flavouring is not possible at present. Considering the genotoxic potential as well as numerous data gaps that need to be closed for a full risk assessment, the SKLM is concerned about the safety of acetaldehyde as a flavouring substance. For reasons of precautionary consumer protection, the SKLM considers that the use of acetaldehyde as a food additive should be re-evaluated.

Whisker spots on polar bears reveal increasing fluctuating asymmetry - Caila E. Kucheravy; Jane M. Waterman; James D. Roth (Mammalian Biology, 2022)

Investigating the combination of plasma amyloid-beta and geroscience biomarkers on the incidence of clinically meaningful cognitive decline in older adults - Wan-Hsuan Lu; Kelly Virecoulon Giudici; John E. Morley; Sophie Guyonnet; Angelo Parini; Geetika Aggarwal; Andrew D. Nguyen; Yan Li; Randall J. Bateman; Bruno Vellas; Philipe de Souto Barreto; Bruno Vellas; et al. (GeroScience, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Assessment of PM2.5, TVOCs, comfort parameters, and volatile organic solvents of paint at carpenter workshop and exposure to residential houses in Deir Ballout in Palestine - S. Jodeh; A. Chakir; Y. Massad; E. Roth (International Journal of Environmental Science and Technology, 2022)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Contribution to the ongoing discussion on fluoride toxicity - Sabine Guth; Stephanie Hüser; Angelika Roth; Gisela Degen; Patrick Diel; Karolina Edlund; Gerhard Eisenbrand; Karl-Heinz Engel; Bernd Epe; Tilman Grune; Volker Heinz; Thomas Henle; et al. (Archives of Toxicology, 2021)
Since the addition of fluoride to drinking water in the 1940s, there have been frequent and sometimes heated discussions regarding its benefits and risks. In a recently published review, we addressed the question if current exposure levels in Europe represent a risk to human health. This review was discussed in an editorial asking why we did not calculate benchmark doses (BMD) of fluoride neurotoxicity for humans. Here, we address the question, why it is problematic to calculate BMDs based on the currently available data. Briefly, the conclusions of the available studies are not homogeneous, reporting negative as well as positive results; moreover, the positive studies lack control of confounding factors such as the influence of well-known neurotoxicants. We also discuss the limitations of several further epidemiological studies that did not meet the inclusion criteria of our review. Finally, it is important to not only focus on epidemiological studies. Rather, risk analysis should consider all available data, including epidemiological, animal, as well as in vitro studies. Despite remaining uncertainties, the totality of evidence does not support the notion that fluoride should be considered a human developmental neurotoxicant at current exposure levels in European countries.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Systematic Review and Meta-analysis of Methodological Quality in In Vivo Animal Studies of Subarachnoid Hemorrhage - Basil E. Grüter; Davide Croci; Salome Schöpf; Edin Nevzati; Donato d’Allonzo; Jacqueline Lattmann; Tabitha Roth; Benjamin Bircher; Carl Muroi; Gilles Dutilh; Hans Rudolf Widmer; Nikolaus Plesnila; et al. (Translational Stroke Research, 2020)

Toxicity of fluoride: critical evaluation of evidence for human developmental neurotoxicity in epidemiological studies, animal experiments and in vitro analyses - Sabine Guth; Stephanie Hüser; Angelika Roth; Gisela Degen; Patrick Diel; Karolina Edlund; Gerhard Eisenbrand; Karl-Heinz Engel; Bernd Epe; Tilman Grune; Volker Heinz; Thomas Henle; et al. (Archives of Toxicology, 2020)
Recently, epidemiological studies have suggested that fluoride is a human developmental neurotoxicant that reduces measures of intelligence in children, placing it into the same category as toxic metals (lead, methylmercury, arsenic) and polychlorinated biphenyls. If true, this assessment would be highly relevant considering the widespread fluoridation of drinking water and the worldwide use of fluoride in oral hygiene products such as toothpaste. To gain a deeper understanding of these assertions, we reviewed the levels of human exposure, as well as results from animal experiments, particularly focusing on developmental toxicity, and the molecular mechanisms by which fluoride can cause adverse effects. Moreover, in vitro studies investigating fluoride in neuronal cells and precursor/stem cells were analyzed, and 23 epidemiological studies published since 2012 were considered. The results show that the margin of exposure (MoE) between no observed adverse effect levels (NOAELs) in animal studies and the current adequate intake (AI) of fluoride (50 µg/kg b.w./day) in humans ranges between 50 and 210, depending on the specific animal experiment used as reference. Even for unusually high fluoride exposure levels, an MoE of at least ten was obtained. Furthermore, concentrations of fluoride in human plasma are much lower than fluoride concentrations, causing effects in cell cultures. In contrast, 21 of 23 recent epidemiological studies report an association between high fluoride exposure and reduced intelligence. The discrepancy between experimental and epidemiological evidence may be reconciled with deficiencies inherent in most of these epidemiological studies on a putative association between fluoride and intelligence, especially with respect to adequate consideration of potential confounding factors, e.g., socioeconomic status, residence, breast feeding, low birth weight, maternal intelligence, and exposure to other neurotoxic chemicals. In conclusion, based on the totality of currently available scientific evidence, the present review does not support the presumption that fluoride should be assessed as a human developmental neurotoxicant at the current exposure levels in Europe.

Reassessing Potential for Exotic Larch in Northern United States - David I Maass; Lloyd C Irland; James L Anderson; Kenneth M Laustsen; Michael S Greenwood; Brian E Roth (Journal of Forestry, 2020)
Abstract Field measurements of operational plantations and research plots demonstrate that growth rates of exotic larches in unmanaged stands can exceed 12 m3 per hectare per year in Maine and elsewhere. This paper briefly reviews the recent history of exotic larch (Larix decidua, L. kaempferi, and L. × marschlinsii) in northeastern United States and Canada. Stands can be commercially thinned as early as 15 years; further thinnings add to significant volume accumulation, based on stand table projections. Genetic development of the hybrid (L. × marschlinsii) could yield additional volume. Even at current low stumpage values, exotic larch plantations offer positive returns at realistic discount rates. In map form, we report a current inventory of known trials and operational plantings across the Northern United States, including adjacent Canada.

Concurrent isolation of hepatic stem cells and hepatocytes from the human liver - Serene M. L. Lee; Cristina Bertinetti-Lapatki; Tobias S. Schiergens; Karl-Walter Jauch; Adrian B. Roth; Wolfgang E. Thasler (In Vitro Cellular & Developmental Biology - Animal, 2020)
Hepatocytes differentiated from induced pluripotent stem cells or stem cells have the potential to be representative in vitro models of the human liver for research as well as early safety assessment programs. However, up until now, there has been no definitive proof that differentiated hepatocytes recapitulate the phenotype and functional characteristics of primary hepatocytes from the same individual. Thus, a method for the concurrent isolation of hepatocytes and hepatic stem cells is presented here to provide the cells necessary for the evaluation of the required benchmarking. The method presented here generated high-quality hepatocytes with a purity of 94 ± 1% and a high percentage viability of 79 ± 2%. Furthermore, the hepatic stem cells isolated were found to be actively proliferating and have a purity of 98 ± 1%. Thus, these isolated cells can be used as a powerful tool for the validation of differentiated hepatocyte in vitro models.

Maternal-Child Exposures to Persistent Organic Pollutants in Dhaka, Bangladesh - Michael Leung; Therese Haugdahl Nøst; Frank Wania; Eszter Papp; Dorte Herzke; Abdullah Al Mahmud; Daniel E. Roth (Exposure and Health, 2020)

Correction to: Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

Irritable Bowel Syndrome, Immune Fitness, and Insomnia: Results from an Online Survey Among People Reporting Sleep Complaints - Smedra Abdulahad; Hendrikje Huls; Stephanie Balikji; Aurora J. A. E. van de Loo; Thomas Roth; Joris C. Verster (Sleep and Vigilance, 2019)

Sex Differences in Early Postnatal Microglial Colonization of the Developing Rat Hippocampus Following a Single-Day Alcohol Exposure - M. J. Ruggiero; K. E. Boschen; T. L. Roth; A. Y. Klintsova (Journal of Neuroimmune Pharmacology, 2018)

Characterization of a newly isolated freshwater Eustigmatophyte alga capable of utilizing far-red light as its sole light source - Benjamin M. Wolf; Dariusz M. Niedzwiedzki; Nikki Cecil M. Magdaong; Robyn Roth; Ursula Goodenough; Robert E. Blankenship (Photosynthesis Research, 2018)

Influence of browsing damage and overstory cover on regeneration of American beech and sugar maple nine years following understory herbicide release in central Maine - Arun K. Bose; Robert G. Wagner; Brian E. Roth; Aaron R. Weiskittel (New Forests, 2018)

Climate change effects on livestock in the Northeast US and strategies for adaptation - A. N. Hristov; A. T. Degaetano; C. A. Rotz; E. Hoberg; R. H. Skinner; T. Felix; H. Li; P. H. Patterson; G. Roth; M. Hall; T. L. Ott; L. H. Baumgard; et al. (Climatic Change, 2018)

The effects of warming and ocean acidification on growth, photosynthesis, and bacterial communities for the marine invasive macroalga Caulerpa taxifolia - Alexandra J. Roth‐Schulze; Torsten Thomas; Peter Steinberg; Marty R. Deveney; Jason E. Tanner; Kathryn H. Wiltshire; Stephanie Papantoniou; John W. Runcie; C. Frederico D. Gurgel (Limnology and Oceanography, 2018)
Caulerpa taxifolia is a pantropical green benthic marine macroalga, and one of the best known marine invasive species in temperate coastal habitats. In Australia, this species has been introduced to seven estuaries along New South Wales and one in South Australia. How this alga will perform under future climate change scenarios is however not well defined. This study experimentally assessed the effects of ocean acidification and global warming on the growth, photosynthetic performance and the bacterial community on two populations of C. taxifolia , one native and one invasive. A range of complex significant interactive effects between pH, temperature, and initial plant size on the growth of C. taxifolia were observed, but no effect of population origin and photosystem II (PSII) fluorescence quantum yield parameters were detected. No significant effects of the treatment combinations were observed on bacterial community richness or diversity. Only one bacterial species out of 1087 present on the algae showed significant changes between pH treatments at high temperature (24°C). This bacterium belonged to the genus Planctomyces and its relative abundance was more than 10 times higher in samples with low pH compared to the control. Higher plant growth was observed under all higher pCO 2 and lower pH conditions suggesting that C. taxifolia will benefit from climate change, posing a potential higher risk in invaded locations.

The Impact of Having a 15-min Break With and Without Consuming an Energy Drink on Prolonged Simulated Highway Driving - Joris C. Verster; Aurora J. A. E. van de Loo; Adriana C. Bervoets; Loes Mooren; Thomas Roth (Sleep and Vigilance, 2017)

Mainstreaming the social sciences in conservation - Nathan J. Bennett; Robin Roth; Sarah C. Klain; Kai M. A. Chan; Douglas A. Clark; Georgina Cullman; Graham Epstein; Michael Paul Nelson; Richard Stedman; Tara L. Teel; Rebecca E. W. Thomas; Carina Wyborn; et al. (Conservation Biology, 2017)
Despite broad recognition of the value of social sciences and increasingly vocal calls for better engagement with the human element of conservation, the conservation social sciences remain misunderstood and underutilized in practice. The conservation social sciences can provide unique and important contributions to society's understanding of the relationships between humans and nature and to improving conservation practice and outcomes. There are 4 barriers—ideological, institutional, knowledge, and capacity—to meaningful integration of the social sciences into conservation. We provide practical guidance on overcoming these barriers to mainstream the social sciences in conservation science, practice, and policy. Broadly, we recommend fostering knowledge on the scope and contributions of the social sciences to conservation, including social scientists from the inception of interdisciplinary research projects, incorporating social science research and insights during all stages of conservation planning and implementation, building social science capacity at all scales in conservation organizations and agencies, and promoting engagement with the social sciences in and through global conservation policy‐influencing organizations. Conservation social scientists, too, need to be willing to engage with natural science knowledge and to communicate insights and recommendations clearly. We urge the conservation community to move beyond superficial engagement with the conservation social sciences. A more inclusive and integrative conservation science—one that includes the natural and social sciences—will enable more ecologically effective and socially just conservation. Better collaboration among social scientists, natural scientists, practitioners, and policy makers will facilitate a renewed and more robust conservation. Mainstreaming the conservation social sciences will facilitate the uptake of the full range of insights and contributions from these fields into conservation policy and practice.

Invasive earthworms interact with abiotic conditions to influence the invasion of common buckthorn (Rhamnus cathartica) - Alexander M. Roth; Timothy J. S. Whitfeld; Alexandra G. Lodge; Nico Eisenhauer; Lee E. Frelich; Peter B. Reich (Oecologia, 2015)

Nanosecond pulsed electric fields modulate the expression of Fas/CD95 death receptor pathway regulators in U937 and Jurkat Cells - Larry E. Estlack; Caleb C. Roth; Gary L. Thompson; William A. Lambert; Bennett L. Ibey (Apoptosis, 2014)

Resident plant diversity and introduced earthworms have contrasting effects on the success of invasive plants - Timothy J. S. Whitfeld; Alexander M. Roth; Alexandra G. Lodge; Nico Eisenhauer; Lee E. Frelich; Peter B. Reich (Biological Invasions, 2014)

Impact of raw pig slurry and pig farming practices on physicochemical parameters and on atmospheric N2O and CH4 emissions of tropical soils, Uvéa Island (South Pacific) - E. Roth; P. Gunkel-Grillon; L. Joly; X. Thomas; T. Decarpenterie; I. Mappe-Fogaing; C. Laporte-Magoni; N. Dumelié; G. Durry (Environmental Science and Pollution Research, 2014)

Multilocation Corn Stover Harvest Effects on Crop Yields and Nutrient Removal - Douglas L. Karlen; Stuart J. Birrell; Jane M. F. Johnson; Shannon L. Osborne; Thomas E. Schumacher; Gary E. Varvel; Richard B. Ferguson; Jeff M. Novak; James R. Fredrick; John M. Baker; John A. Lamb; Paul R. Adler; et al. (BioEnergy Research, 2014)

A Simplified Approach for Simultaneous Measurements of Wavefront Velocity and Curvature in the Heart Using Activation Times - Nachaat Mazeh; David E. Haines; Matthew W. Kay; Bradley J. Roth (Cardiovascular Engineering and Technology, 2013)

Selected Trace Elements in the Sacramento River, California: Occurrence and Distribution - H. E. Taylor; R. C. Antweiler; D. A. Roth; C. N. Alpers; P. Dileanis (Archives of Environmental Contamination and Toxicology, 2012)

Live chilling of Atlantic salmon: physiological response to handling and temperature decrease on welfare - A. Foss; E. Grimsbø; E. Vikingstad; R. Nortvedt; E. Slinde; B. Roth (Fish Physiology and Biochemistry, 2012)

p53-dependent regulation of Mcl-1 contributes to synergistic cell death by ionizing radiation and the Bcl-2/Bcl-XL inhibitor ABT-737 - Katrin E. Tagscherer; Anne Fassl; Tabea Sinkovic; Stephanie E. Combs; Wilfried Roth (Apoptosis, 2012)

Autistic Traits Below the Clinical Threshold: Re-examining the Broader Autism Phenotype in the 21st Century - E. Sucksmith; I. Roth; R. A. Hoekstra (Neuropsychology Review, 2011)

Porous EH and EH-PEG Scaffolds as Gene Delivery Vehicles to Skeletal Muscle - Erin E. Falco; Martha O. Wang; Joshua A. Thompson; Joshua M. Chetta; Diana M. Yoon; Erik Z. Li; Mangesh M. Kulkami; Sameer Shah; Abhay Pandit; J. Scott Roth; John P. Fisher (Pharmaceutical Research, 2011)

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

Rs710521[A] on chromosome 3q28 close to TP63 is associated with increased urinary bladder cancer risk - Marie-Louise Lehmann; Silvia Selinski; Meinolf Blaszkewicz; Michael Orlich; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truss; Holger Gerullis; Thomas Otto; Dimitri Barski; et al. (Archives of Toxicology, 2010)

The roles of social domains, behavioral risk, health care resources, and chlamydia in spatial clusters of US cervical cancer mortality: not all the clusters are the same - Ping Du; Allison Lemkin; Brenda Kluhsman; Jin Chen; Robert E. Roth; Alan MacEachren; Craig Meyers; John J. Zurlo; Eugene J. Lengerich (Cancer Causes & Control, 2010)

Role of kappa-opioid receptors in the effects of salvinorin A and ketamine on attention in rats - Christina L. Nemeth; Tracie A. Paine; Joseph E. Rittiner; Cécile Béguin; F. Ivy Carroll; Bryan L. Roth; Bruce M. Cohen; William A. Carlezon (Psychopharmacology, 2010)

Adaptive clustering of airborne LiDAR data to segment individual tree crowns in managed pine forests - H. Lee; K. C. Slatton; B. E. Roth; W. P. Cropper (International Journal of Remote Sensing, 2010)

Cryptic seedling herbivory by nocturnal introduced generalists impacts survival, performance of native and exotic plants - Sharon Y. Strauss; Maureen L. Stanton; Nancy C. Emery; Carrie A. Bradley; Alexandra Carleton; Dylan R. Dittrich-Reed; Olivia A. Ervin; Levi N. Gray; Andrew M. Hamilton; Jennifer Harrington Rogge; Skye D. Harper; Kimberley Cook Law; et al. (Ecology, 2009)
Although much of the theory on the success of invasive species has been geared at escape from specialist enemies, the impact of introduced generalist invertebrate herbivores on both native and introduced plant species has been underappreciated. The role of nocturnal invertebrate herbivores in structuring plant communities has been examined extensively in Europe, but less so in North America. Many nocturnal generalists (slugs, snails, and earwigs) have been introduced to North America, and 96% of herbivores found during a night census at our California Central Valley site were introduced generalists. We explored the role of these herbivores in the distribution, survivorship, and growth of 12 native and introduced plant species from six families. We predicted that introduced species sharing an evolutionary history with these generalists might be less vulnerable than native plant species. We quantified plant and herbivore abundances within our heterogeneous site and also established herbivore removal experiments in 160 plots spanning the gamut of microhabitats. As 18 collaborators, we checked 2000 seedling sites every day for three weeks to assess nocturnal seedling predation. Laboratory feeding trials allowed us to quantify the palatability of plant species to the two dominant nocturnal herbivores at the site (slugs and earwigs) and allowed us to account for herbivore microhabitat preferences when analyzing attack rates on seedlings. The relationship between local slug abundance and percent cover of five common plant taxa at the field site was significantly negatively associated with the mean palatability of these taxa to slugs in laboratory trials. Moreover, seedling mortality of 12 species in open‐field plots was positively correlated with mean palatability of these taxa to both slugs and earwigs in laboratory trials. Counter to expectations, seedlings of native species were neither more vulnerable nor more palatable to nocturnal generalists than those of introduced species. Growth comparison of plants within and outside herbivore exclosures also revealed no differences between native and introduced plant species, despite large impacts of herbivores on growth. Cryptic nocturnal predation on seedlings was common and had large effects on plant establishment at our site. Without intensive monitoring, such predation could easily be misconstrued as poor seedling emergence.

Prediction of forest canopy light interception using three‐dimensional airborne LiDAR data - H. Lee; K. C. Slatton; B. E. Roth; W. P. Cropper (International Journal of Remote Sensing, 2009)

Keeping the blood flowing—plasminogen activator genes and feeding behavior in vampire bats - Åsa Tellgren-Roth; Katharina Dittmar; Steven E. Massey; Cecilia Kemi; Christian Tellgren-Roth; Peter Savolainen; Leslie A. Lyons; David A. Liberles (The Science of Nature, 2009)

BLOC1S2 interacts with the HIPPI protein and sensitizes NCH89 glioblastoma cells to apoptosis - Georg Gdynia; Judith Lehmann-Koch; Sebastian Sieber; Katrin E. Tagscherer; Anne Fassl; Hanswalter Zentgraf; Shu-Ichi Matsuzawa; John C. Reed; Wilfried Roth (Apoptosis, 2008)

Mercury and Organic Carbon Dynamics During Runoff Episodes from a Northeastern USA Watershed - P. F. Schuster; J. B. Shanley; M. Marvin-Dipasquale; M. M. Reddy; G. R. Aiken; D. A. Roth; H. E. Taylor; D. P. Krabbenhoft; J. F. DeWild (Water, Air, & Soil Pollution, 2007)

Quantifying the effects of voluntary contraction and inter-stimulus interval on the human soleus H-reflex - Richard B. Stein; Kristen L. Estabrooks; Steven McGie; Michael J. Roth; Kelvin E. Jones (Experimental Brain Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Preserved dynamic cerebral autoregulation in the middle cerebral artery among persons with migraine - M. Reinhard; E. Wehrle-Wieland; M. Roth; W. D. Niesen; J. Timmer; C. Weiller; A. Hetzel (Experimental Brain Research, 2007)

WAY-100635 is a potent dopamine D4 receptor agonist - Benjamin R. Chemel; Bryan L. Roth; Blaine Armbruster; Val J. Watts; David E. Nichols (Psychopharmacology, 2006)

Determinants of predation risk in small wintering birds: the hawk’s perspective - Timothy C. Roth; Steven L. Lima; William E. Vetter (Behavioral Ecology and Sociobiology, 2006)

Dose-dependent retrograde facilitation of verbal memory in healthy elderly after acute oral lorazepam administration - Nunzio Pomara; Thomas M. Facelle; Amy E. Roth; Lisa M. Willoughby; David J. Greenblatt; John J. Sidtis (Psychopharmacology, 2006)

Seasonal cycle in vitamin A1/A2-based visual pigment composition during the life history of coho salmon (Oncorhynchus kisutch) - S. E. Temple; E. M. Plate; S. Ramsden; T. J. Haimberger; W.-M. Roth; C. W. Hawryshyn (Journal of Comparative Physiology A, 2006)

BUBBLE – an Urban Boundary Layer Meteorology Project - M. W. Rotach; R. Vogt; C. Bernhofer; E. Batchvarova; A. Christen; A. Clappier; B. Feddersen; S.-E. Gryning; G. Martucci; H. Mayer; V. Mitev; T. R. Oke; et al. (Theoretical and Applied Climatology, 2005)

CHARACTERISTICS OF A HUMAN PROSTATE STROMAL CELL LINE RELATED TO ITS USE IN A STROMAL–EPITHELIAL COCULTURE MODEL FOR THE STUDY OF CANCER CHEMOPREVENTION - LENA DIAW; MARK ROTH; DEBRA A. SCHWINN; MARY E. d'ALELIO; LISA J. GREEN; JOSEPH A. TANGREA (In Vitro Cellular & Developmental Biology - Animal, 2005)

Sex differences in the acquisition of IV methamphetamine self-administration and subsequent maintenance under a progressive ratio schedule in rats - Megan E. Roth; Marilyn E. Carroll (Psychopharmacology, 2004)

The economic value of recreational fisheries in Nordic countries - A.‐L. Toivonen; E. Roth; S. Navrud; G. Gudbergsson; H. Appelblad; B. Bengtsson; P. Tuunainen (Fisheries Management and Ecology, 2004)
Recreational fishing, whether free or at cost, has an economic value. This value was measured in five Nordic countries based on a contingent valuation mail survey. Regression models were used to identify demographic characteristics, types of fishing patterns and differences in the countries’ management regimes that can explain both actual fishing expenditure and willingness to pay for the non‐market benefits by persons participating in fishing or enjoying the benefits derived by it. Net benefit, i.e. willingness to pay over and above actual expenditure was highest amongst those fishing. In Denmark, the small number of generalist fishermen get the highest benefit. In Finland results are mixed but sports fishermen benefit on average even more than generalists. Urban sports fishing raises the highest benefit in Iceland while in Norway the benefit is more equally spread, with occasional anglers and women reaping the least. In Sweden the mean benefit is the lowest in the Nordic countries but evenly distributed among categories of fishermen. In the Nordic countries combined, nationality explains willingness to pay as being Norwegian or Finnish increases benefit and being Icelandic reduces it. The non‐use value of recreational fisheries was elicited through posing questions on willingness to pay for the preservation of the existence of current fish stocks and current quality of recreational fishing to persons participating in fishing or enjoying the benefits derived from it. For those not fishing or people in general, the power of the models to explain willingness to pay for the existence of recreational fisheries was very weak. The benefit, i.e. willingness to pay, is higher if somebody in the household fishes. Educated, young, urban, well‐off citizens also put value on the non‐use of the resource.

Using Environmental Stressor Information to Predict the Ecological Status of Maryland Non-tidal Streams as Measured by Biological Indicators - J. H. Vølstad; N. E. Roth; G. Mercurio; M. T. Southerland; D. E. Strebel (Environmental Monitoring and Assessment, 2003)

DMT1: A mammalian transporter for multiple metals - Michael D. Garrick; Kevin G. Dolan; Craig Horbinski; Andrew J. Ghio; Dennis Higgins; Michael Porubcin; Elizabeth G. Moore; Lucille N. Hainsworth; Jay N. Umbreit; Marcel E. Conrad; Lee Feng; Agnieska Lis; et al. (BioMetals, 2003)

Phosphorus budget and phosphorus availability in soils under organic and conventional farming - F. Oehl; A. Oberson; H.U. Tagmann; J.M. Besson; D. Dubois; P. Mäder; H.-R. Roth; E. Frossard (Nutrient Cycling in Agroecosystems, 2002)

The Occurrence and Distribution of Selected Trace Elements in the Upper Rio Grande and Tributaries in Colorado and Northern New Mexico - H. E. Taylor; R. C. Antweiler; D. A. Roth; T. I. Brinton; D. B. Peart; D. F. Healy (Archives of Environmental Contamination and Toxicology, 2001)

Methodological, conceptual and sampling practices in surveying recreational fisheries in the Nordic countries - experiences of a valuation survey - E. Roth; A. L. Toivonen; S. Navrud; B. Bengtsson; G. Gudbergsson; P. Tuunainen; H. Appelblad; G. Weissglas (Fisheries Management and Ecology, 2001)

Methodological, conceptual and sampling practices in surveying recreational fisheries in the Nordic countries – experiences of a valuation survey - E. Roth; A. L. Toivonen; S. Navrud; B. Bengtsson; G. Gudbergsson; P. Tuunainen; H. Appelblad; G. Weissglas (Fisheries Management and Ecology, 2001)
The planning and initial phases of a joint Nordic project for the valuation of recreational fisheries is described. The economic value of recreational fisheries was taken to include non‐market value as well as the traditional market value. The design of the survey was similar for each country so as to facilitate future comparison. However, initially there were difficulties in defining categories of recreational fishermen in the different countries. Other background information also had to be adapted to national circumstances. National population registers were used as the sampling frames. The effect of this on the responses from a valuation survey is discussed. Accessibility to population register data varies by country and so do possibilities for random sampling. Legal constraints were faced when implementing a centralised mailing system.

Survival of introduced Tuber melanosyorum at two sites in Israel as measured by occurrence of mycorrhizas - V. Kagan-Zur; S. Freeman; Y. Luzzati; Nurit Roth-Bejerano; E. Shabi (Plant and Soil, 2001)

Distribution of Inorganic Mercury in Sacramento River Water and Suspended Colloidal Sediment Material - D. A. Roth, H. E. Taylor, J. Domagalsk (Archives of Environmental Contamination and Toxicology, 2001)

Carbon mineralization and microbial activity in a field site trial used for 14 C turnover experiments over a period of 30 years - M. Stemmer; K. Roth; E. Kandeler (Biology and Fertility of Soils, 2000)

Acquisition of oral phencyclidine self-administration in rhesus monkeys: effect of sex - M. E. Carroll; M. E. Roth; R. K. Voeller; P. D. Nguyen (Psychopharmacology, 2000)

Comparison of either norepinephrine-uptake inhibitors or phentermine combined with serotonergic agents on food intake in rats - N. E. Rowland; M. Marshall; J. D. Roth (Psychopharmacology, 2000)

Interaction of cholera toxin and Escherichia coli heat-labile enterotoxin with glycoconjugates from rabbit intestinal brush border membranes: Relationship with ABH blood group determinants - Luis E. Balanzino; José L. Barra; Estela M. Galváin; German A. Roth; Clara G. Monferran (Molecular and Cellular Biochemistry, 1999)

Improved mRNA in situ hybridization on formaldehyde-fixed and paraffin-embedded tissue using signal amplification with different haptenized tyramides - E. J. M. Speel; Parvin Saremaslani; Jürgen Roth; Anton H. N. Hopman; Paul Komminoth (Histochemistry and Cell Biology, 1998)

Inhibition of nitric oxide synthase attenuates lipopolysaccharide-induced fever without reduction of circulating cytokines in guinea-pigs - Joachim Roth; Birgit Störr; Karlheinz Voigt; E. Zeisberger (Pflügers Archiv - European Journal of Physiology, 1998)

Efficacy of administration of dexfenfluramine and phentermine, alone and in combination, on ingestive behavior and body weight in rats - Jonathan D. Roth; N. E. Rowland (Psychopharmacology, 1998)

Isolation of a petite mutant from a histidine auxotroph of Candida albicans and its characterization - Z. Roth-Ben Arie; Z. Altboum; I. Berdicevsky; E. Segal (Mycopathologia, 1998)

Fever and production of cytokines in response to repeated injections of muramyl dipeptide in guinea-pigs - Joachim Roth; Stephen J. Hopkins; Margaret E. Hoadley; Anke Tripp; Tunai Aslan; Birgit Störr; Giamal N. Luheshi; E. Zeisberger (Pflügers Archiv - European Journal of Physiology, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Behavioral ecology ofMyiopharus doryphorae (riley) andM. aberrans (townsend), tachinid parasitoids of the colorado potato beetle - E. R. López; L. C. Roth; D. N. Ferro; D. Hosmer; A. Mafra-Neto (Journal of Insect Behavior, 1997)

Carbon dioxide exchange across the walls of arterioles: Implication for the location of the medullary chemoreceptors - J. Milton Adams; Christine Banka; Walter E. Wojcicki; Allan C. Roth (Annals of Biomedical Engineering, 1988)

Ultrastructure of the capsule of Klebsiella pneumoniae and slime of Enterobacter aerogenes revealed by freeze etching - E. Louise Springer; Ivan L. Roth (Archives of Microbiology, 1973)

Timing applications for control of potato aphids on Long Island - W. A. Rawlins; R. W. Roth; J. E. Dewey (American Journal of Potato Research, 1943)